2012
DOI: 10.1155/2012/717213
|View full text |Cite
|
Sign up to set email alerts
|

The Toronto Extremity Salvage Score in Unoperated Controls: An Age, Gender, and Country Comparison

Abstract: The Toronto Extremity Salvage Score (TESS) is widely used for the functional assessment of patients following surgery for musculoskeletal tumours. The aim of this study was to determine if there are gender and/or age-specific changes, unrelated to surgery, that may influence this score and the appropriateness of the questions. The TESS for lower limb was carried out in two different countries to see if there was variation between them. There were no statistically significant differences between the scores obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 10 publications
(11 reference statements)
0
29
4
Order By: Relevance
“…It is simple enough to accept why some of these variables will affect physical functioning following limb salvage. With increasing age, physical function also deteriorates , as shown in Clayers paper. Females have less muscle mass and strength compared to males ; rehabilitation and being reliant on upper body strength (in the case of a lower limb salvage) and may explain why they experience more disability.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is simple enough to accept why some of these variables will affect physical functioning following limb salvage. With increasing age, physical function also deteriorates , as shown in Clayers paper. Females have less muscle mass and strength compared to males ; rehabilitation and being reliant on upper body strength (in the case of a lower limb salvage) and may explain why they experience more disability.…”
Section: Discussionmentioning
confidence: 89%
“…In the same study, Davis looked at patient age and gender but no significant difference was found between groups. Clayers paper looked at the TESS of healthy individuals looking at the variations in outcome score by age, sex, and nationality . They found that the TESS score decreases with age in normal individual but found no difference in patient gender or nationality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to discern whether patients who are diagnosed and treated at an older age are truly at risk for poorer functional outcomes, as age at diagnosis and age at time of survey are strongly correlated. Loss of physical function is common with the normal process of aging, as demonstrated in a study of healthy, unoperated adults that revealed increasing age was correlated with lower TESS scores . However, it must also be considered that patients undergoing treatment for ES at a younger age are better able to accommodate psychologically and physically to their treatment‐related changes and thus report an elevated self‐perception of function.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients mentioned their associated comorbidities and age-related decreased functional status. As a baseline, in an otherwise healthy population TESS demonstrates an age-related decline, with scores of 98% in people in their 30s and 76% to 88% for those in their 70s (18). The most common physical complaint in our patients was mild edema, especially after prolonged standing.…”
Section: Qol Outcomesmentioning
confidence: 62%